Traumatic Autobiographical Memories: Preliminary fMRI Findings Among Men With Histories of Childhood Sexual Abuse. Issue 3 (May 2022) - Chiasson, Carley; Moorman, Jessie; Romano, Elisa; Smith, Andra
Childhood sexual abuse (CSA) is associated with autobiographical memory (AM) disturbances. AM is important for future thinking, sense of self, and coping with negative emotions. CSA is under-researched among men, with research examining long-term neural correlates limited even further. This study explored the neural correlates of re-experiencing traumatic/negative memories to examine the influence of CSA on AM into adulthood. Fifteen males who experienced CSA, with and without posttraumatic stress disorder (PTSD; CSA+PTSD, n = 6; CSA–PTSD, n = 9) and control males without CSA histories nor PTSD ( n = 11) completed a script-driven imagery paradigm during functional magnetic resonance imaging (fMRI). Males with CSA histories, with and without PTSD, processed their negative autobiographical memories with less activation compared to control males. The CSA+PTSD group of males had less activation in the left superior occipital, left superior parietal and left parahippocampal gyri compared to control participants. The CSA–PTSD group had reduced activation in the same regions to a lesser extent. This study provides preliminary empirical evidence to suggest CSA impacts AM for traumatic experiences, and the impact is notable even for men who experienced CSA but do not have PTSD. This study highlights the need for more research with men who have experienced CSA, so that, we can fully understand the neural correlates of emotional memories, and better support the mental health and continued wellness of men who experienced CSA.